Computer-based training system for cataract surgery. (December 2013) - Dequidt, Jérémie; Courtecuisse, Hadrien; Comas, Olivier; Allard, Jérémie; Duriez, Christian; Cotin, Stéphane; Dumortier, Élodie; Wavreille, Olivier; Rouland, Jean-François
This paper describes a single simulation framework to perform interactive cataract surgery simulations. Contributions includes advanced bio-mechanical models and intensive use of modern graphics hardware to provide fast computation times. Surgical devices are replicated and located in a real-time thanks to infrared tracking. Combination of a high-fidelity simulation and actual surgical tools are able to improve surgeon immersion while training. Preliminary tests have been performed by experienced ophthalmologists to qualitatively assess the face-validity of the simulator and the faithfulness of the behavior of the anatomical structures as well as the interactions with the surgical tools.